2018
DOI: 10.1186/s12889-018-5429-2
|View full text |Cite
|
Sign up to set email alerts
|

Bacteria and poisonous plants were the primary causative hazards of foodborne disease outbreak: a seven-year survey from Guangxi, South China

Abstract: BackgroundFoodborne diseases are a worldwide public health problem. However, data regarding epidemiological characteristics are still lacking in China. We aimed to analyze the characteristics of foodborne diseases outbreak from 2010 to 2016 in Guangxi, South China.MethodsA foodborne disease outbreak is the occurrence of two or more cases of a similar foodborne disease resulting from the ingestion of a common food. All data are obtained from reports in the Public Health Emergency Report and Management Informati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 12 publications
1
9
0
Order By: Relevance
“…Such as food categories implicated in foodborne disease outbreaks were 24 categories in the USA (14), no “a variety of foods”. Fruit and its products (including preserved fruit and preserves) was the second frequently reported exposed food, meat and meat products was only third in our analysis, this result is similar to that of other provinces in China (15, 16), however, the major proportion of cases of foodborne illness in western developed countries are associated with foods of animal origin (17). In the US and the EU, leafy greens, tomatoes, melons, legumes and grains were major food types in non-animal origin of foods that cause foodborne diseases (18, 19), and our analysis also shows that vegetable and its products is a very important food category of exposed food.…”
Section: Discussionsupporting
confidence: 85%
“…Such as food categories implicated in foodborne disease outbreaks were 24 categories in the USA (14), no “a variety of foods”. Fruit and its products (including preserved fruit and preserves) was the second frequently reported exposed food, meat and meat products was only third in our analysis, this result is similar to that of other provinces in China (15, 16), however, the major proportion of cases of foodborne illness in western developed countries are associated with foods of animal origin (17). In the US and the EU, leafy greens, tomatoes, melons, legumes and grains were major food types in non-animal origin of foods that cause foodborne diseases (18, 19), and our analysis also shows that vegetable and its products is a very important food category of exposed food.…”
Section: Discussionsupporting
confidence: 85%
“…In 2012, OzFoodNet (Foodborne disease surveillance and response across Australia) sites reported 2180 outbreaks of gastrointestinal illness affecting 40,547 individuals, resulting in 955 hospitalizations and 131 associated deaths [17]. In South China, from 2010 to 2016, a total of 138 FBD outbreaks were reported (mean of 19.7 outbreaks annually), involving 3348 cases and 46 deaths [18].…”
Section: Discussionmentioning
confidence: 99%
“…A study conducted by Ting-ting [32] in China showed that, between 2002 and 2011, most deaths due to FBD outbreaks occurred in homes. In another study conducted in China, Li et al [18] showed that schools (42.7%) and homes (32.6%) were the main sites of FBD outbreaks. These findings highlight the importance of investment in sanitary conditions and education for the population.…”
Section: Discussionmentioning
confidence: 99%
“…A study conducted by Ting-ting [27] in China showed that most deaths due to FBD outbreaks occurred in homes between 2002 and 2011. In another study conducted in China, Li et al [28] have shown that schools (42.7%) and homes (32.6%) were the main sites of FBD outbreaks.…”
Section: Data From the Scientific Literaturementioning
confidence: 96%